Inventarisasi Jenis-Jenis Ikan yang Ditemukan di Estuari Sungai Tanjung Belimbing Kabupaten Sambas - Ari Hepi Yanti, Abu Khoir Ridwan, Tri Rima Setyawati (Jurnal Protobiont, 2016)
Potential of fishery in the estuarine ecosystem is quite high, for example in the area of Tanjung Belimbing River in Subdistrict of Paloh, Sambas Regency. This research aims to find out the species of fish that found in these waters. The research was carried out for three months from February to April 2015 in Tanjung Belimbing River estuary. Fish samples were taken at four stations and categorized based on the environmental condition. There were 18 species of fish found in the location which are grouped into 13 families i.e. Ariidae, Carangidae, Clupiedae, Cynoglossidae, Engraulidae, Leiognathidae, Mullidae, Platycephalidae, Pristigasteridae, Sciaenidae, Synodontidae, Tetraodontidae and Trichiuridae. Fishes from family Carangidae and Engraulidae were dominant in this research with 3 species.